Synthesis and Characterization of a New Photoluminescent Material Tris(5-Choloro 8-Hydroxyquinoline) Lanthanum La(5-Clq)3. (2016) - Kumar, Rahul; Nemala, Siva Sankar; Bhargava, Parag
Abstract: A new photoluminescence material, tris (5-Choloro 8-hydroxy quinoline) lanthanum has been synthesized and characterized by different techniques. The prepared material La(5-Clq)3 was characterized for structural, thermal and photoluminescence analysis. Structural analysis of this material was done by fourier transformed infrared spectroscopy (FTIR) and mass spectroscopy. Thermal analysis of this material was done by thermal gravimetric analysis (TGA) shows the thermal stability up to 180°C.Absorption and emission spectra of the material was measured by UV-visible spectroscopy and photoluminescence spectroscopy. Solution of this material La(5-Clq)3 in ethanol showed absorption peaks at 350nm and 395nm respectively which may be attributed due to ( π – π∗) transitions. The photoluminescence spectra of La (5-Clq)3 in ethanol solution showed intense peak at 515 nm.